2019
DOI: 10.1038/s41598-019-56006-9
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and compassion toward other species decrease with evolutionary divergence time

Abstract: Currently the planet is inhabited by several millions of extremely diversified species. Not all of them arouse emotions of the same nature or intensity in humans. Little is known about the extent of our affective responses toward them and the factors that may explain these differences. Our online survey involved 3500 raters who had to make choices depending on specific questions designed to either assess their empathic perceptions or their compassionate reactions toward an extended photographic sampling of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 32 publications
8
102
1
4
Order By: Relevance
“…It seems clear that some wildlife species are far more significant to humans than others ( Herzog and Burghardt, 1988 ), perhaps linked to their evolutionary closeness (e.g., primates, and particularly the great apes; Gunnthorsdottir, 2001 ; Miralles et al, 2019 ) or because of their cultural, aesthetic, or affective attributes favoring more interest and attention toward them. Interest and attention favor people’s attitudes for conserving these species, differently from others without a transcendental meaning for social groups.…”
Section: Emotions and Wildlife Conservationmentioning
confidence: 99%
“…It seems clear that some wildlife species are far more significant to humans than others ( Herzog and Burghardt, 1988 ), perhaps linked to their evolutionary closeness (e.g., primates, and particularly the great apes; Gunnthorsdottir, 2001 ; Miralles et al, 2019 ) or because of their cultural, aesthetic, or affective attributes favoring more interest and attention toward them. Interest and attention favor people’s attitudes for conserving these species, differently from others without a transcendental meaning for social groups.…”
Section: Emotions and Wildlife Conservationmentioning
confidence: 99%
“…Participants attributed more mental states and cognitive processes to the macaque and the elephant, and their responses were more homogenous. Miralles and colleagues [98] showed that empathy and compassion toward other species (animal and non-animal) decrease with evolutionary divergence time. Urquiza-Haas and Kotrschal [9] argued that as the phylogenetic distance increases between a human and the species it observes, anthropomorphism reduces or becomes reflective rather than automatic (i.e., visceral).…”
Section: Discussionmentioning
confidence: 99%
“…We also expect that education will lead to less anthropomorphism or to reflective anthropomorphism. Participants are also expected to show more anthropomorphism for species that are phylogenetically close to humans [98].…”
Section: Introductionmentioning
confidence: 99%
“…A major issue of such an approach to animal ethics is, however, that it remains human-centered (i.e., anthropocentrism) and focused on human thought (i.e., anthropomorphism). Indeed, the human empathy tree appears to be different to the phylogenetic tree, meaning that human empathy toward other organisms is not equally distributed within the tree of life (Miralles et al, 2019). Why, for instance, are cognitive capacities considered to be highly important in defining which animals can be used for human benefit?…”
Section: Introductionmentioning
confidence: 99%